Ethical and legal problems arising from off-label use of medical devices and some solution recommendations - Perihan Elif Ekmekçi; Berna Arda (KARE Publishing, 2018)
The off-label use of medical devices is becoming increasingly widespread. Though the off-label use of drugs has been controlled with the establishment of legal and ethical rules, similar regulations have not been implemented for medical devices. Legal gaps in this field, and the broad initiative granted to physicians have led to the emergence of problems in practice, and physicians are vulnerable to potential criminal sanctions that may emerge as a consequence of these off-label applications. Since the off-label use of medical devices cannot rely on scientifically proven, evidence-based information, evaluation of the risks creates critically important ethical problems that may have serious deleterious effects, despite the good intent of a physician tying to be helpful. During the process of obtaining informed consent from the patient for the off-label use of a device, the physician has crucial responsibilities. The ethical responsibilities of physicians particularly increase in vulnerable patient groups that should be protected from harm. In addition to the physician, the family members who make decisions on behalf of the patient also assume some responsibilities. The development of ethical norms and guidelines enforced by legal regulations concerning this issue, an effective role for ethics committees in the decision-making process, and collaboration between patients, scientists, nongovernmental organizations, medical device companies, specialists in the field of medical ethics, and legal authorities will be important in solving this problem.